Towards a new agenda for vocation. Issue 1 (18th February 2021) - Snyder, Timothy
Abstract: This article addresses the contemporary use of Luther's theology of vocation as a theological script for meaning‐making. Lived experiences of modern work demonstrate that many social structures and constraints challenge the notion of vocation in its classic form. A new agenda is called for and initial steps are taken to suggest a new way forward.